A survey to assess awareness about fixed dose combinations (FDCs) among pharmacists in two Central Kashmir Districts, Srinagar and Budgam, Kashmir, India - Mir, Shakeel Ahmad (International Journal of Basic & Clinical Pharmacology, 2017)
Background: FDCs are highly popular in Indian pharmaceutical market. The FDCs have both advantages as well as disadvantages. To be advantageous WHO guidelines for the manufacture and use of FDCs must be strictly followed. Irrational use of FDCs is a major public health problem and leads to increased risk of adverse drug events, higher treatment costs and antimicrobial resistance. FDCs as well as other single component drugs cannot be used rationally unless everyone involved directly or indirectly in the health care profession is involved. Pharmacist is a coordinator between different members of healthcare team and the patients. Hence, his role in safe use of medicines is important. The present study was undertaken to assess the knowledge of pharmacists about FDCs. Methods: A descriptive questionnaire survey was conducted in various government and private pharmacies of two Central Kashmir Districts, Srinagar and Budgam, aiming to assess the knowledge of pharmacists about FDCs. The questionnaires were distributed randomly among 79 pharmacists, out of which 60 returned the completed questionnaire. Results: 55.00% of the respondents knew the basic facts about FDCs. 96.66% knew that FDCs reduced the cost of therapy and 93.33% were aware that FDCs improve patient compliance. 60% answered incorrectly when asked about effect of FDCs on cumulative toxicity. Almost equal percentage (63.33%) answered incorrectly when asked about rationality and ADR profile of FDCs. 83.33% knew that it is difficult to know the offending agent in case ADRs occur after FDC use.78.33% respondents thought that all FDCs are approved by drug regulatory authorities. Conclusions: The study showed that pharmacists had not the enough knowledge about FDCs. Pharmacy students in their formative years of learning should be taught to promote rational use of FDCs as they are the future custodians of technical information on the products available on their domestic market.